Rapid 3D Avatar Creation System Using a Single Depth Camera - Lim, Hwasup; Ahn, Sang Chul; Kang, Junseok (2019 26TH IEEE CONFERENCE ON VIRTUAL REALITY AND 3D USER INTERFACES (VR), 2019)
We present a rapid and fully automatic 3D avatar creation system that can produce personalized 3D avatars within two minutes using a single depth camera and a motorized turntable. The created 3D avatar is able to make all the details of facial expressions and whole body motions including fingers. To our best knowledge, it is the first completely automatic system that can generate realistic 3D avatars in the common 3D file format, which is ready for the direct use in virtual reality applications or various services.